The Scenario Approach to Establishing GR Communications in Higher Education Institutions - FEDYUNIN, Dmitriy V.; LOCHAN, Sergey A.; AVTONOMOVA, Svetlana A.; KUTYRKINA, Lyudmila. V.; MINTUSOV, Igor E. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).09, 2019)
Education and professional training are at the basis of human development and social progress. This strategic significance of education is enhanced manifold in the present-day age of information and economics of knowledge. A rapid development and technological upgrading of Russian higher education suggests the need for the implementation of modern information and communication technologies in higher education institutions and for the development of a communications system complete with a set of structures that influence their activities in this or that way. Considering that the quality and efficiency of Russian educational organizations largely depend on the policies pursued by public and local authorities, there is a need in the organization and implementation of an effective way of interacting with them. This article focuses on the nature of GR (Government Relations) communications in higher education institutions and carries out an analysis of the prospects and practical application of one of the GR technologies, namely, corporate social responsibility of educational institutions using the example of foreign universities. Furthermore, the study highlights the need and prospects for using the scenario approach when planning and implementing GR communications in educational institutions.